Profitability of Manufacturing Firms in Indonesia Amidst the Pandemic - Sholikha Oktavi Khalifaturofi'ah; Rahmat Setiawan (ETIKONOMI, 2024)
Research Originality: In the realm of manufacturing firms, the pursuit of profitability remains a foremost concern. This paper distinguishes itself through its innovative approach, integrating key factors such as liquidity, leverage, activity, and the influence of the COVID-19 pandemic. Utilizing panel regression analysis, the study scrutinizes Indonesia's total manufacturing firms to shed light on this critical issue.Research Objectives: This study primarily aims to evaluate the profitability of manufacturing firms in Indonesia. It specifically delves into the impact of liquidity, leverage, and activity measures on profitability, while also examining how the COVID-19 pandemic factors into this equation.Research Methods: Employing a quantitative approach, this study utilizes panel data gathered from 134 manufacturing firms in Indonesia spanning from 2018 to 2023. The analysis relies on a panel regression model to draw insights.Empirical Results: The analysis yields significant findings. Notably, leverage demonstrates a negative and statistically significant influence on manufacturing firms' profitability, whereas firm activity shows a positive and statistically significant effect. Conversely, liquidity and the COVID-19 pandemic appear to have negligible impacts on profitability.Implications: These findings hold critical implications for policymakers and practitioners within Indonesia's manufacturing sector. To bolster the profitability of manufacturing firms, policymakers should prioritize reducing leverage and fostering increased company activity, possibly through amplified sales efforts.JEL Classification: G32, G33, G01, L60How to Cite:Khalifaturofi’ah, S. O., & Setiawan, R. (2024). Profitability of Manufacturing Firms in Indonesia Amidst the Pandemic. Etikonomi, 23(2), 497-510. htttps://doi.org/10.15408/etk.v23i2.35169.